Improved production of thermostable pectinase from novel Bacillus siamensis (BIOSMNF45) using computational-conventional approach - Anushka Satpathy; Koel Mukherjee; Vinod Kumar Nigam (Scientific Reports)
Abstract The demand for thermostable pectinase in the global commercial market has expanded progressively at a rapid pace. Many industrial processes are operated at elevated temperatures to break down plant polysaccharides (pectin) owing to the significant use of thermotolerant pectinase. Therefore, the study aimed to optimize the medium constituents for enhanced pectinase production from a thermotolerant pectinolytic bacteria (BIOSMNF45) in combination with the one-variable-at-a-time (OVAT) and response surface methodology (RSM). The isolated BIOSMNF45 with high thermostable pectinase activity was identified as Bacillus siamensis by 16S rRNA sequencing. OVAT technique was used in the preliminary screening of different variables (incubation time, incubation temperature, pH, carbon%, organic nitrogen%, and inorganic nitrogen%) before proceeding to the RSM study. The OVAT result showed that the highest production of thermostable pectinase was attained at 1.00% (w/v) carbon (pectin), 0.40% organic nitrogen (yeast extract), pH 6.00, temperature 45℃ and an agitation of 150 rpm for 24 h incubation. Furthermore, the RSM outcomes revealed that the optimized fermentation conditions boost the thermostable pectinase yield from Bacillus siamensis (BIOSMNF45) by 6.7 folds. It also suggested that the percentage of carbon and temperature showed the highest impact on improved pectinase production compared to other factors.